Pengaruh Modal Sosial dan Modal Sumber Daya Manusia Terhadap Intensi Berwirausaha: Peran Modal Psikologis Sebagai Mediasi - Gefira Amalia Husein; Akhmad Darmawan; Hermin Endratno; Arini Hidayah (Jurnal Ilmiah Global Education, 2026)
This study examines the influence of social capital and human capital on theentrepreneurial intentions of former Indonesian migrant workers (PMI purna), withpsychological capital positioned as a mediating variable. Grounded in the Theory ofPlanned Behavior (TPB), the research analyzes how social networks, skills, workexperience, and psychological readiness shape entrepreneurial intentions amongreturnees. A descriptive quantitative approach was employed through thedistribution of Likert-scale questionnaires to 100 purposively selected respondentsfrom a popolation of 476 former Indonesian migrant workers in Cihonje Village,Banyumas Regency. The four variables, namely social capital, human capital,psychological capital, and entrepreneurial intention, were measured using validatesindicators and analiyzed with PLS-SEM.The finding indicate that social capital and human capital positively andsignificantly influence entrepreneurial intentions. Psychological capital alsodemonstrates a strong direct effect and serves as a partial mediator thatstrengthens the relationship between both forms of capital and entrepreneurialintention. The R-Square value of 0,803 reflects strong predictive power of themodel, while the value of 0,604 for psychological capital confirms its essentialmediating role. These results highlight the importance of social support,competence development, and psychological readiness in fostering entrepreneurialbehavior. The study recommends empowerment programs that integrate social,skill-bassed and psychological components to enchance the economicindependence of former Indonesian migrant workers.